Should early improvement be re‐defined to better predict the maintenance of response in first‐episode schizophrenia patients?. (8th September 2012) - Schennach, R.; Riesbeck, M.; Mayr, A.; Seemüller, F.; Maier, W.; Klingberg, S.; Heuser, I.; Klosterkötter, J.; Gastpar, M.; Schmitt, A.; Sauer, H.; Schneider, F.; et al.
<x xml:space="preserve">Abstract</x> Schennach R, Riesbeck M, Mayr A, Seemüller F, Maier W, Klingberg S, Heuser I, Klosterkötter J, Gastpar M, Schmitt A, Sauer H, Schneider F, Jäger M, Wölwer W, Gaebel W, Möller H‐J, Riedel M. Should early improvement be re‐defined to better predict the maintenance of response in first‐episode schizophrenia patients? Objective: To evaluate the predictive validity of early response in first‐episode schizophrenia within a 1‐year follow‐up trial and to compare the resulting cutoff to the currently proposed early response definition (20% improvement by week 2). Method: Receiver operator characteristic (ROC) analyses were used to identify the predictive validity of the psychopathological improvement of treatment from week 1 to week 8, regarding the maintenance of response until week 52 as well as to define the most reasonable cutoff in 132 first‐episode patients. The Youden Index (maximum of sensitivity and specificity) was used to compare the newly developed and the commonly used early response definition. Results: Starting with week 6, a reasonable validity to predict the maintenance of response was found (area under the curve = 0.721) with the best fitting cutoff being a 51.6% PANSS total score improvement. Using this cutoff 74 patients (56%) were correctly identified to become responder and maintain response during follow‐up (sensitivity: 0.747). The Youden Index was higher applying the newly developed early response cutoff featuring higher specificity compared to the commonly used early response definition. Conclusion: Regarding long‐term treatment, it seems more appropriate to base predictions of the patient's maintenance of response not before 6 weeks of treatment.